2015
DOI: 10.1186/s12993-015-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and therapeutic applications of electromagnetic therapy in Parkinson’s disease

Abstract: Electromagnetic therapy is a non-invasive and safe approach for the management of several pathological conditions including neurodegenerative diseases. Parkinson’s disease is a neurodegenerative pathology caused by abnormal degeneration of dopaminergic neurons in the ventral tegmental area and substantia nigra pars compacta in the midbrain resulting in damage to the basal ganglia. Electromagnetic therapy has been extensively used in the clinical setting in the form of transcranial magnetic stimulation, repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 145 publications
0
27
0
1
Order By: Relevance
“…Moreover, previous data showed that microtubule depolymerization or stabilization also changed the number and length of primary cilia. The production of cytoplasmic soluble tubulin caused an increase in ciliary length, while a limited supply of soluble tubulin after treatment with the microtubule-stabilizing drug Taxol led to shortened cilia or the complete absence of cilia (Kim et al, 2010;Sharma et al, 2011). 4 | THE PRIMARY CILIUM AS AN ELECTROMAGNETIC FIELD SENSOR Electromagnetic fields (EMFs) have long been considered to be one of the promising alternatives to drug-based therapies for bone disease (Friedenberg & Brighton, 1966), cancer (Vadalà et al, 2016) and wound healing (Saliev, Mustapova, Kulsharova, Bulanin, & Mikhalovsky, 2014).…”
Section: Interconnection Of the Primary Cilium And The Cytoskeletonmentioning
confidence: 99%
“…Moreover, previous data showed that microtubule depolymerization or stabilization also changed the number and length of primary cilia. The production of cytoplasmic soluble tubulin caused an increase in ciliary length, while a limited supply of soluble tubulin after treatment with the microtubule-stabilizing drug Taxol led to shortened cilia or the complete absence of cilia (Kim et al, 2010;Sharma et al, 2011). 4 | THE PRIMARY CILIUM AS AN ELECTROMAGNETIC FIELD SENSOR Electromagnetic fields (EMFs) have long been considered to be one of the promising alternatives to drug-based therapies for bone disease (Friedenberg & Brighton, 1966), cancer (Vadalà et al, 2016) and wound healing (Saliev, Mustapova, Kulsharova, Bulanin, & Mikhalovsky, 2014).…”
Section: Interconnection Of the Primary Cilium And The Cytoskeletonmentioning
confidence: 99%
“…Low frequency Pulsed Electro Magnetic Fields (PEMF) have been found to produce a variety of beneficial effects and therefore successfully employed as adjunctive therapy for a wide range of clinical conditions [1][2][3][4]. Although properly configured electromagnetic signals demonstrate to regulate major cellular functions, including proliferation, differentiation and apoptosis [5][6][7], little is known about their biological mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Thus to ensure a good outcome, it is required that the functional capacity of the affected brain region should be restored [6]. Anninos P. et al(2007) [19] reported that TMS increases the release of dopamine in the striatum and frontal cortex, which in turn improves PD symptoms including motor performance.…”
Section: Transcranial Magnetic Stimulation Versus Electrical Vestibulmentioning
confidence: 99%
“…TMS has been used to measure CNS adaptation and its relationship to changes in neural control and function [5]. The rationale for the application of TMS The patients' responses to TMS included a feeling of relaxation, partial or complete disappearance of muscular ache and L-dopa-induced dyskinesias as well as rapid reversal of visuos-patial impairment [6,7]. Clinical applications of TMS were first reported by Barker and colleagues who stimulated the brain, spinal cord and peri-pheral nerves using TMS with low or no pain.…”
mentioning
confidence: 99%